(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Aristotle, in his essay on friendship intellectually considers the state of friendship in its ramifications right from the qualities of character and the conditions necessary for true friendship to the human problems related to it. The originality and universality of Aristotle’s thoughts can be seen by a comparison of his view on friendship with those of his mentor Plato and with later writers such as Montaigne and Shakespeare and by the fact that his views are still relevant today.